1) MULTIDIMENSIONAL SCALING FOR CREDIT DEFAULT SWAP (CDS): EVIDENCE FROM OECD COUNTRIES - Ayhan KAPUSUZOGLU; Nildag Basak CEYLAN (Buletin ştiinţific: Universitatea din Piteşti. Seria Ştiinţe Economice, 2018)
The aim of this study is to analyze the similarities and differences between the OECD countries in terms of the change in CDS risk premiums. Accordingly, CDS risk premiums of the related countries are taken on a monthly basis for the 30/06/2011 - 30/09/2018 period. The Euclidean distances are calculated using Multidimensional Scaling Analysis. As a result of the study, the most similar (close) country pairs are calculated according to their euclidean distances. The results of the analysis show that New Zealand-Australia, Estonia-Austria, Slovakia-Netherlands, Finland-Denmark and Germany-France are the most similar country pairs whereas Slovenia-Turkey, Netherlands-Turkey, Russia-Norway, Russia-Mexico and Slovakia-Turkey are the most dissimilar country pairs. According to the results obtained; Mexico, Russia, Chile and Turkey are the countries which are decomposed significantly from the other OECD countries. Moreover, the countries which are geographically close to each other are also very similar in terms of the change in the economic risk level.